2016
DOI: 10.3758/s13414-016-1132-5
|View full text |Cite
|
Sign up to set email alerts
|

Action-specific judgment, not perception: Fitts’ law performance is related to estimates of target width only when participants are given a performance score

Abstract: Proponents of the action-specific account of perception and action posit that participants perceive their environment relative to their capabilities. For example, softball players who batted well judge the ball as being larger compared to players who did not hit as well. In the present study, we examined this issue in the context of a well-known speedaccuracy movement task that can be examined in the laboratory, repetitive Fitts aiming. In the Fitts task, a performer moved as quickly and as accurately as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Consequently, even in the case of grasping responses, we agree with Bub et al that "very strong evidence is needed" (p. 66) before reaching a firm conclusion that even a subset of compatibility effects in choice-reaction tasks is a consequence of limb-specific motor representations rather than abstract response codes. Regardless of whether such effects are due predominantly to spatial coding (Proctor & Vu, 2006) or to affordances (Gibson, 1979), it is apparent that the decisions and actions a person tends to make directly, or automatically, are determined by various factors including task goals, object properties, and the environmental context in which the person is operating (e.g., Zelaznik & Forney, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, even in the case of grasping responses, we agree with Bub et al that "very strong evidence is needed" (p. 66) before reaching a firm conclusion that even a subset of compatibility effects in choice-reaction tasks is a consequence of limb-specific motor representations rather than abstract response codes. Regardless of whether such effects are due predominantly to spatial coding (Proctor & Vu, 2006) or to affordances (Gibson, 1979), it is apparent that the decisions and actions a person tends to make directly, or automatically, are determined by various factors including task goals, object properties, and the environmental context in which the person is operating (e.g., Zelaznik & Forney, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in cognitive processing and/or task familiarity could have contributed to the observed differences in predicted MTs [ 29 , 30 ]. For example, Zelaznik and Forney [ 31 ], found that perception of Fitts’s task difficulty (target width) was only related to motor performance if participants received a score after they performed the task. This finding indicates that knowledge of performance, in addition to motor experience is important for the accuracy of perceptual judgments (also see [ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
“…If action-specific scaling effects truly reflect changes in what is perceived in this strong sense, then this has major implications for standard, modular theories of vision, which hold that perception is encapsulated and separate from cognition (Pylyshyn, 1999 ; for a recent review, see Firestone & Scholl, 2015 ). However, a major debate concerning the action-specific account is whether the observed scaling effects reflect judgement rather than perception (Collier & Lawson, 2017 ; Durgin et al, 2009 ; Durgin, Klein, Spiegel, Strawset & Williams, 2012 ; Firestone & Scholl, 2014 ; Zelaznik & Forney, 2016 ; for reviews, see Firestone, 2013 ; Firestone & Scholl, 2015 ; Philbeck & Witt, 2015 ; Proffitt & Linkenauger, 2013 ; Witt, 2011 , 2016 ). Specifically, participants’ responses may not reflect differences in what they actually perceive; rather, their spatial estimates may be affected by nonperceptual influences such as their beliefs about the purpose of the experiment.…”
mentioning
confidence: 99%